Cavity ring down spectroscopy of water vapour near 750 nm: a test of the HITRAN2020 and W2020 line lists. (18th August 2022) - Vasilchenko, S.; Mikhailenko, S.N.; Campargue, A.
Abstract : Cavity ring down spectroscopy (CRDS) is used to measure with unprecedented sensitivity and accuracy the weak water vapour spectrum in the 13, 171–13, 417 cm −1 region. A total of more than 1400 water lines are rovibrationally assigned to four isotopologues in natural isotopic abundance (H2 16 O, H2 18 O, H2 17 O and HD 16 O), leading to the determination of 151 new levels and correction of 160 levels. The review of previous experimental works in the region is discussed. The comparison to the recent HITRAN2020 spectroscopic databases and to the W2020 line lists [Furtenbacher et al . J. Phys. Chem. Ref. Data 49 (2020) 043103; doi:10.1063/5.0030680 ] shows important discrepancies both for line positions and line intensities. A significant fraction of the W2020 line positions is inaccurate and shows deviations compared to measurements largely exceeding their claimed error bars. Line intensities are poorly predicted by available ab initio calculations in the considered region. A recommended line list mostly based on the present CRDS measurements is proposed. GRAPHICAL ABSTRACT: UF0001